Revision of the Oocyclus Sharp of Brazil with description of ten new species(Coleoptera: Hydrophilidae: Laccobiini) - Clarkson, Bruno; Short, Andrew E.z. (Zootaxa, 2012)
The Brazilian species of the water scavenger beetle genus Oocyclus Sharp, 1882 are revised. Fourteen species are recog-nized, including ten described as new from southern and southeastern Brazil: Oocyclus acuru sp. n., O. aeneus sp. n., O.alterosa sp. n., O. caparao sp. n., O. flexus sp. n., O. itapecori sp. n., O. itapicum sp. n., O. rotundus sp. n., O. xanthus sp.n., and O. yubai sp. n. New records for two of the three previously recorded Brazilian species, O. decorus (Kuwert) andO. fryanus Balfour-Browne, are given. One species, O. iguazu (Oliva), is newly recorded from the country as well as fromParaguay. The holotypes of O. fryanus and O. schubarti d’Orchymont are redescribed. A key and high-resolution imagesof each species are provided. Consistent with the biology of other members of the genus, all species are found in rocks seeps and other hygropetric habitats.